2021
DOI: 10.3390/polym13060864
|View full text |Cite
|
Sign up to set email alerts
|

Development and Analysis of Mechanical Properties of Caryota and Sisal Natural Fibers Reinforced Epoxy Hybrid Composites

Abstract: In recent years, natural fiber reinforced polymer composites have gained much attention over synthetic fiber composites because of their many advantages such as low-cost, light in weight, non-toxic, non-abrasive, and bio-degradable properties. Many researchers have found interest in using epoxy resin for composite fabrication over other thermosetting and thermoplastic polymers due to its dimensional stability and mechanical properties. In this research work, the mechanical and moisture properties of Caryota an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…This type of natural fiber is widely used in the construction industry, such as panels, doors, and shuttering plates [ 76 ]. Atmakuri et al [ 77 ] fabricated a modified composite consist of sisal and caryota fiber as shown in Figure 11 . Mechanical and moisture properties was studied.…”
Section: Resultsmentioning
confidence: 99%
“…This type of natural fiber is widely used in the construction industry, such as panels, doors, and shuttering plates [ 76 ]. Atmakuri et al [ 77 ] fabricated a modified composite consist of sisal and caryota fiber as shown in Figure 11 . Mechanical and moisture properties was studied.…”
Section: Resultsmentioning
confidence: 99%
“…The glass fiber and natural fibers were mixed thoroughly and then poured on a glass mold with dimensions of 500 × 300 × 4 mm already containing an amount of epoxy resin. The remaining resin was then spread over the mat, and a 15 kg load was held above the sample and left to cure for 24 h. Atmakuri et al [ 82 ] employed the hand lay-up technique in the fabrication of Caryota and sisal natural fiber hybrid epoxy composites. Firstly, the epoxy resin and hardener were mixed in a ratio of 10:1.…”
Section: Processing Of Epoxy-based Natural Fiber Polymer Composite Ma...mentioning
confidence: 99%
“…Epoxy products are used in many industries and a variety of applications for materials that require durability in terms of chemical and mechanical characteristics [1], [2] heat-resistance [3], [4], electrical conductivity [5] and sound insulation [6] due to their ability to maintain technical performance over the whole life span. Such materials are used as coatings, paints, composites, adhesives, insulation materials, etc.…”
Section: Introductionmentioning
confidence: 99%